PUBLIC PERCEPTION OF THE POSITIVE AND NEGATIVE IMPACTS OF ONLINE LOANS IN THE DIGITAL ERA IN SERANG CITY - Helmas Septiyo Hadi; Abu Naim; Sena Atmaja; Mardi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The rapid expansion of digital technology in Indonesia has transformed financial services, notably through online lending (pinjaman online/pinjol) that provides fast and practical access to funds. This study investigates community perceptions of the positive and negative impacts of online loans in Serang City, a semi-urban area with increasing internet penetration but relatively low digital financial literacy. Using a mixed-methods design, the research combines quantitative surveys of 348 respondents with qualitative interviews of the Serang City Communication and Information Office (Diskominfo) and the Banten Regional Police. Descriptive analysis shows that residents recognise significant benefits of legal online loans, such as quick disbursement, flexible use, and support for micro-business capital (mean score 38.11 on a 1–5 Likert scale). However, perceptions of negative impacts are substantially higher (mean score 44.80), highlighting concerns over predatory interest rates, aggressive collection practices, lack of transparency, and misuse of personal data. Behavioural data (mean score 44.13) reveal generally cautious attitudes, with respondents checking platform legality and reading terms before borrowing. Qualitative findings confirm that low digital literacy and economic vulnerability heighten community risk, while illegal pinjol are viewed as cybercrime requiring cross-sector enforcement and stronger national regulation. The study recommends integrated digital literacy programs, stricter oversight of lending platforms, and enhanced cooperation between government agencies, law enforcement, and community institutions to protect consumers and promote responsible fintech use.